Aleksander Mikhailovich Lyapunovs (1857–1918) Kharkov Period Of Scientific And Educational Activities (Pedagogy of Higher and Secondary Education, 2013)
Bobrytska G. S., Kushlakova N. N Aleksander Mikhailovich Lyapunovs (1857–1918) Kharkov Period Of Scientific And Educational Activities.The paper summarizes the Lyapunov’s scientific and pedagogical views in Kharkov period of his life, reconstructs his activities at the Kharkov Mathematical Society, defines his relationship to the system of the student’s training and supervision at military and technical schools (a system of rehearsals).
Keywords: Aleksander Mikhailovich Lyapunov; the Kharkov Mathematical Society; teaching activities; the problem of high school; rehearsal; motivation